The Invasion of Alternanthera philoxeroides Increased Soil Organic Carbon in a River and a Constructed Wetland With Different Mechanisms - Yang, Ruirui; Li, Ke; Fang, Jiaohui; Quan, Quan; Zhang, Chao; Liu, Jian (Frontiers in Ecology and Evolution, 2020)
Wetlands have been considered as a vital reservoir of global carbon and are vulnerable to plant invasion. However, the influence mechanism of plant invasion on soil organic carbon (SOC) in wetlands remains unclear. In this study, we investigated SOC, soil physicochemical properties, and soil microbes in the invaded and non-invaded sites in Xinxue River and Xinxue River Constructed Wetland to research the effects of Alternanthera philoxeroides invasion on SOC and explore the related mechanisms. The invasion of A. philoxeroides increased SOC content and density in both the river and the constructed wetland. SOC in the two types of wetlands was positively correlated with moisture content and negatively correlated with bulk density, dissolved oxygen, water temperature, soil temperature, and pH. The invasion decreased the dissolved oxygen in the river and the soil temperature in the constructed wetland which might be the explanation for the increase of SOC in the two types of wetlands. In the river, the decrease of dissolved oxygen caused by plant invasion could alter the microbial community and limit the decomposition of SOC by microbes, which was confirmed by the increase of microbial α diversity indices and the correlations between soil microbial community in the river and dissolved oxygen showed by RDA analysis. The invasion of A. philoxeroides significantly shifted the soil microbial community in the constructed wetland. Redundancy analysis showed that the variation of soil microbial community structure in the constructed wetland could be mainly explained by soil pH and soil temperature. The decrease of soil temperature in the constructed wetland might inhibit microbial activities and result in the accumulation of SOC. In addition, the indicator species reflecting soil microbial community shifted by plant invasion were highly correlated with SOC, suggesting that the variation of indicator species between invaded sites and non-invaded sites might be another reason for the difference in SOC. The study indicates that A. philoxeroides invasion might increase the carbon storage in rivers and constructed wetlands with different mechanisms.